History, power, communication, journalism : Beyond the "traditional" critical approach - Reig, Ramón, (El Profesional de la información, 2019)
This article is not going to limit itself to presenting the traditional dualist view of good versus bad (the good is repre sented by average citizens manipulated by the bad, which is the capitalist media-driven society). Such views have their origin point in the Marxist or neo-Marxist school of thought, which was strictly adhered to by the (first generation) of the Frankfurt School, and it is known as critical thinking. This research supports the fundamentals of critical thinking, but additionally argues that "critical thinking" exists also to criticize itself, to overcome it, and to enter into what we call "Complex Structural Approach" (CSA). The Power is, to a large extent, the market in evolution and involution and acts today through the marginalization of universal historical memory and philosophy, among other knowledge, and is replaced by infoxication. The western citizen is not completely unaware of its dependency. The virtual-intelligent society of the 21th century connects with one of the innate characteristics of the individual: his selfishness, whether it is positive or destructive behavior, in various formats and in varying degrees.